2019
DOI: 10.1002/ijc.32685
|View full text |Cite
|
Sign up to set email alerts
|

SI‐CLP inhibits the growth of mouse mammary adenocarcinoma by preventing recruitment of tumor‐associated macrophages

Abstract: Chitinase‐like proteins (CLP) are chitin‐binding proteins that lack chitin hydrolyzing activity, but possess cytokine‐like and growth factor‐like properties, and play crucial role in intercellular crosstalk. Both human and mice express two members of CLP family: YKL‐40 and stabilin‐1 interacting chitinase‐like protein (SI‐CLP). Despite numerous reports indicating the role of YKL‐40 in the support of angiogenesis, tumor cell proliferation, invasion and metastasis, the role of its structurally related protein SI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…54 Another Clever-1 ligand, stabilin-1-interacting chitinase-like protein (SI-CLP), inhibits tumour growth in a mouse breast cancer model by blocking the cytokine-induced recruitment of TAMs and altering the cell composition of the TME. 55 As the expression of SI-CLP has been reported to be markedly downregulated or absent in some human breast cancers, 55 targeting Clever-1 might again prove a worthwhile strategy.…”
Section: Potential Mechanism(s) Of Action Of Clever-1 In Tumour Growthmentioning
confidence: 99%
“…54 Another Clever-1 ligand, stabilin-1-interacting chitinase-like protein (SI-CLP), inhibits tumour growth in a mouse breast cancer model by blocking the cytokine-induced recruitment of TAMs and altering the cell composition of the TME. 55 As the expression of SI-CLP has been reported to be markedly downregulated or absent in some human breast cancers, 55 targeting Clever-1 might again prove a worthwhile strategy.…”
Section: Potential Mechanism(s) Of Action Of Clever-1 In Tumour Growthmentioning
confidence: 99%
“…These typical M2 markers are surface receptors that are responsible for the non-inflammatory clearance of microenvironment from apoptotic bodies, ECM components, soluble mediators of activation of cancer cells and angiogenesis (6)(7)(8)(9)(10)(11)(12). In addition to scavenging function (10,11,13), stabilin-1 acts as an intracellular sorting receptor that targets chitinase-like proteins SI-CLP and YKL-39 to the secretory pathway (14)(15)(16)(17)(18)(19). SI-CLP and YKL-39, in turn, regulate monocyte recruitment and angiogenesis (15,17,18,20).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to scavenging function (10,11,13), stabilin-1 acts as an intracellular sorting receptor that targets chitinase-like proteins SI-CLP and YKL-39 to the secretory pathway (14)(15)(16)(17)(18)(19). SI-CLP and YKL-39, in turn, regulate monocyte recruitment and angiogenesis (15,17,18,20).…”
Section: Introductionmentioning
confidence: 99%
“…Blocking the effect of chemokines is an important method to inhibit the recruitment of TAMs, and the current research targets are mostly CCL2/CCR2 ( 52 , 111 ). The inhibition of the CCL2/CCR2 axis can reduce the mobilization of bone marrow mononuclear cells, thereby reducing the infiltration of macrophages in the breast ( 112 , 113 ). Studies have shown that trabectedine and bortezomib can inhibit the recruitment of macrophages by reducing the content of CCL2 in plasma ( 114 ).…”
Section: Tams-based Targeted Therapymentioning
confidence: 99%